Arte, moral y prostitución: Un asunto escabroso en la Nacional de 1897 - Carrasco Garrido, Reyes (Anuario del Departamento de Historia y Teoría del Arte, 1998)
Our end-of-century society didn't agree on the inmorality of some pictorial matters. This happened in the National Exhibition in 1897, where two artists from Valencia, Fillol and Sorolla dared to trespass those limits: prostitution was becaming a topic in painting. Critic was immediate.